VD_FINDINFO Décision / 2012 / 146 vom 15. Februar 2012 - VD Tribunal cantonal (2012)
ORDONNANCE DE CONDAMNATION, SUSPENSION DE LA PROCÉDURE, OPPOSITIONPROCÉDURE | 329 CPP (CH), 354 CPP (CH), 355 CPP (CH), 393 al. 1 let. b CPP (CH)